2016
DOI: 10.1111/infa.12151
|View full text |Cite
|
Sign up to set email alerts
|

Infants' First Words are not Phonetically Specified: Own Name Recognition in British English‐Learning 5‐Month‐Olds

Abstract: By the end of their first year of life, infants’ representations of familiar words contain phonetic detail; yet little is known about the nature of these representations at the very beginning of word learning. Bouchon et al. () showed that French‐learning 5‐month‐olds could detect a vowel change in their own name and not a consonant change, but also that infants reacted to the acoustic distance between vowels. Here, we tested British English‐learning 5‐month‐olds in a similar study to examine whether the acous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 85 publications
1
13
0
Order By: Relevance
“…Bouchon et al (2015) found that infants’ vowel bias at 5 months was driven by spectral distance differences between the individual correct and mispronounced vowel stimuli presented to infants during the experiment. In a direct replication of this study with British‐English‐learning infants, Delle Luche et al (2016) found no evidence for a consonant or vowel bias and weak evidence that infants’ processing of consonants and vowels is driven by acoustic cues, specifically energy information in consonants. Taken together with the results of the current study, we suggest that the inconsistent findings in terms of the role of acoustic/phonetic factors may result from the type of stimuli used.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Bouchon et al (2015) found that infants’ vowel bias at 5 months was driven by spectral distance differences between the individual correct and mispronounced vowel stimuli presented to infants during the experiment. In a direct replication of this study with British‐English‐learning infants, Delle Luche et al (2016) found no evidence for a consonant or vowel bias and weak evidence that infants’ processing of consonants and vowels is driven by acoustic cues, specifically energy information in consonants. Taken together with the results of the current study, we suggest that the inconsistent findings in terms of the role of acoustic/phonetic factors may result from the type of stimuli used.…”
Section: Discussionmentioning
confidence: 59%
“…As development continues, however, the saliency of vowels loses importance to consonants, which are processed more categorically (Fry, Abramson, Eimas, & Liberman, 1962) and therefore provide a more reliable cue to lexical processing. Variation in acoustic/phonetic properties, such as lexical stress which leads to vowel reduction in English or the large number of vowels in Danish, has been suggested to account for the cross‐linguistic variation found in evidence for the consonant bias (Delle Luche, Floccia, Granjeon, & Nazzi, 2016; Floccia et al, 2014; Højen & Nazzi, 2015; see Nazzi et al, 2016 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…The first indications of these links appear before the onset of speech: infants as young as six months can correctly identify the referents of frequently heard words (Bergelson & Swingley, 2012; see also Delle Luche, Floccia, Granjon, & Nazzi, 2016). These early label‐object associations are strengthened incrementally over the long‐term via cross‐situational learning (Smith & Yu, 2008), in which repeated encounters of label‐object co‐occurrences in a variety of contexts eventually lead to long‐term word learning.…”
mentioning
confidence: 99%
“…Furthermore, infants’ attention to vowels has been clearly demonstrated by 6 months, both in word‐form recognition tasks (Bouchon et al., ; cf. Delle Luche et al., ) and native sound category learning (Kuhl et al., ; Polka & Werker, ).…”
Section: Infants’ Speech and Word‐form Representationsmentioning
confidence: 99%
“…Elevenmonth-olds also know the phonological forms of at least some words, as shown when they differentiate spoken lists of common words and slight phonological "mispronunciations" of those words (Hall e & de Boysson-Bardies, 1996;Swingley, 2005;Vihman, Nakai, DePaolis, & Hall e, 2004). Five-month-olds tested on changes to the initial sounds in their own name paint a mixed picture: French infants detected a sound change to their name but only for vowelonset names; English infants did not (Bouchon, Floccia, Fux, Adda-Decker, & Nazzi, 2015;Delle Luche, Floccia, Granjon, & Nazzi, 2017). These studies used unfamiliar talkers, implying that when infants successfully discriminated, they transferred their phonological knowledge into expectations for new voices.…”
Section: Infants' Speech and Word-form Representationsmentioning
confidence: 99%